(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This study aimed to demonstrate the methodological procedure for preparing the booklet entitled "Projeto Águas da Guanabara", the result of research carried out by scholarship holders from the project of the same name. The project was built and promoted by the Federation of Fishermen of the State of Rio de Janeiro (FEPERJ) in partnership with FAPERJ (Foundation for Research Support of the State of Rio de Janeiro), the Secretariat of Science, Technology and Innovation of the State Government of Rio de Janeiro, and the municipal governments of São Gonçalo and Magé. The booklet presents possible practical applications in society. The content of the booklet is divided into three distinct parts. The first part explains what the project is, why it was created and how it will be carried out. The second part consists of a short story with characters, situations and scenarios related to Guanabara Bay, including interesting facts about the mangrove forest and the Águas da Guanabara Project. The third and final part contains an illustrated dictionary and some fun activities, aimed at developing creativity and consolidating the reader’s learning. All material was prepared in simple, easy-to-understand language, with the aim of reaching as many people as possible. The booklet is a viable instrument for bringing academic-scientific knowledge closer to society, in addition to being a means of raising awareness about socio-environmental issues and the possibility of intervention through sustainable actions and Environmental Education. With the proposal of the environmental booklet, it is intended that readers get to know the Águas da Guanabara Project and learn more about Guanabara Bay in an attractive and interactive way, encompassing scientific knowledge and the dissemination of new knowledge, boosting scientific and social development. The booklet is a considerable tool in environmental education, with the aim of training multipliers who can pass on the knowledge acquired. The proposed booklet can be applied to basic education students and others interested in the topic, and is expected to contribute to the conservation of the waters of Guanabara Bay, as well as its flora and fauna.